Implementasi Sistem Pendukung Keputusan Dengan Metode Multi-Attribute Utility Theory Untuk Pemilihan Karyawan Terbaik Di PT Sharp Electronics Indonesia - Loevita Yulian Sari; Dewi Sahara Nasution; Faiz Rafdhi; Nur Kumala Dewi; Warno (Jurnal Sistem Informasi dan E-Bisnis, 2025)
This study developed a Decision Support System (DSS) using the Multi-Attribute Utility Theory (MAUT) method to assist in the process of selecting the best employees at PT Sharp Electronics Indonesia. The system was designed based on criteria such as attendance, discipline, productivity, work ethic, and initiative. The system was evaluated using the Technology Acceptance Model (TAM) approach with 80 respondents from the HRD and management divisions. The evaluation results show that 92.2% of respondents stated that the system is very useful (Perceived Usefulness), 89.6% stated that the system is easy to use (Perceived Ease of Use), 91% demonstrated a positive attitude toward using the system (Attitude Toward Using), and 91.6% expressed a high intention to continue using the system (Behavioral Intention to Use). With these results, the MAUT-based DSS system has proven to be well-received and effective in supporting decision-making processes within the company environment. Keywords—MAUT, TAM, Karyawan, HRD